“Nobody should talk about it”: Fijian health system resilience and the COVID-19 pandemic - McLennan, Sharon; Movono, Apisalome; Thomas-Maude, Johanna; Siliasau, Isoa; Vosanibola, Apolosi (Institute of Development Studies, Massey University)
In April 2021 Fiji made international news with stories of ‘horrific’ health care conditions, including hospital staff and patients without food, hospital operating theatres out of service, and shortages of beds, medicine, equipment, and blood. While Fiji appeared to be relatively well-prepared to respond to COVID-19 and had successfully avoided a major outbreak in 2020, a rapid increase in the number of cases in 2021 quickly overwhelmed the public health system. In this working paper, we draw on the health systems resilience framework of tangible hardware, tangible software, and intangible software to explore the impacts of COVID-19 in Fiji, the underlying causes of the resulting crisis, and the response of the Fijian health sector. We contend that the 2021-22 crisis was no accident, but that over two decades of political instability, multiple smaller crises, chronic under-resourcing, and neglect left the system with limited ability to cope with the pandemic, and potentially insufficient resources to enter a recovery phase post-pandemic. However, this research also highlights the role of intangible resources, including the adaptive practices, collective labour, and sacrifices of health workers drawing on solesolevaki and communal cultural values. We argue these were not only vital to the Fijian pandemic response but may offer a path towards resilience-building in the health system, and for the radical innovation and adaptions necessary to provide a healthy environment and best quality care for Fijians both in ‘normal’ circumstances and in the face of future crises.